Assessment of daily food intake in Allahabad district: a geographical analysis - Amit Kumar Singh,; Pawan Kumar Bhaskar,; V.K.Kumra, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Proper and adequate nutrition is essential for good health of men and women not only in urban areas but also in rural. The food behavior is directly related to nutritional and health status of individual. There is need of sufficient amount of nutrients in the form of daily diet for the maintenance of good health. Many factors, particularly socioeconomic such as living condition and other factors related to dietary intake influence the nutritional status. Malnutrition causes increasing illness, morbidity and mortality as well as diminishing the quality of life (Antia,1989). In this present study an attempt has been made to analyse the socio-economic factors that influence the nutritional status and health of people living in Allahabad district. It is based on primary data collected through personal survey based on randomly chosen samples in the study area. Various statistical methods are used for analysis of the data. Study reveals that dietary intake is higher among respondents of general caste than the other caste. It is also observed that younger women diet intake is slightly better than older women.